Deaf gain : raising the stakes for human diversity - Bauman, H-Dirksen L., 1964-; Murray, Joseph J. (University of Minnesota Press, 2014)
Deaf people are usually regarded by the hearing world as having a lack, as missing a sense. Yet a definition of deaf people based on hearing loss obscures a wealth of ways in which societies have benefited from the significant contributions of deaf people. In this intervention into ongoing debates about disability and what it means to be human, experts from a variety of disciplines - neuroscience, linguistics, bioethics, history, cultural studies, education, public policy, art, and architecture - advance the concept of deaf gain and challenge assumptions about what is normal. Through their articulation of deaf gain, the editors and authors of this volume approach deafness as a distinct way of being in the world, one which opens up perceptions, perspectives, and insights that are less common to the majority of hearing persons. For example, deaf individuals tend to have unique capabilities in spatial and facial recognition, peripheral processing, and the detection of images. And users of sign language, which neuroscientists have shown to be biologically equivalent to speech, contribute toward a robust range of creative expression and understanding. By framing deafness in terms of its intellectual, creative, and cultural benefits, this text recognizes physical and cognitive difference as a vital aspect of human diversity.--description provided by publisher.